(untitled) (Journal of Special Education and Rehabilitation, 2013)
The Institute of Special Education and Rehabilitation, Faculty of Philosophy in Skopje, in 2013 year celebrates the anniversary “20 years from the beginning special education and rehabilitation studies” and in that occasion it is organizing the 4th International Conference with the main topic “Modern aspects of the special education and rehabilitation of persons with disabilities”. The Conference will be held from 17th until 19th of October in Ohrid, the city of UNESCO, also known as Balkan and European Jerusalem. A Book of abstracts and a Book of papers (only from the papers which will be presented) will be published from the Conference. One person can be an author of maximum one paper, and a co-author of maximum three papers. The deadline for submission of the abstracts is 31st of March, 2013 year and the deadline for submission of the whole paper is 31st of May, 2013 year. Abstracts and papers received after the deadline will not be considered and included in the Conference program and in the Book of abstracts and the Book of papers.